Comparative effects of the Mandibular Protraction Appliance in adolescents and adults - Bruno D'Aurea Furquim; Guilherme Janson; Laura de Castro Cabrera Cope; Karina Maria Salvatore Freitas; José Fernando Castanha Henriques
ABSTRACT Objective: The aim of this study was to compare the skeletal, dental, and soft tissue effects of the Mandibular Protraction Appliance (MPA) application in adolescent and adult Class II malocclusion patients. Methods: The sample comprised the pretreatment and posttreatment lateral cephalograms of 39 subjects presenting Class II malocclusion treated with the MPA and fixed appliances. Sample was divided into two groups: Group 1 comprised 23 subjects (10 male; 13 female), at a mean pretreatment age of 11.75 years, with a mean treatment time of 3.32 years; Group 2 included 16 subjects (7 male; 9 female), at a mean pretreatment age of 22.41 years, with a mean treatment time of 4.24 years. Intergroup comparison of the initial and final stages and treatment changes between the groups was performed with t tests, at p< 0.05. Results: The adults showed less significant amounts of skeletal, dentoalveolar and soft tissue changes than the adolescents. There was significantly greater palatal tipping of the maxillary incisors and retrusion of the upper lip in the adolescents. The adult group showed greater mandibular incisor proclination in the posttreatment stage. Conclusion: Adult patients treated with MPA showed less significant amounts of skeletal, dentoalveolar and soft tissue changes than adolescents.